2014
DOI: 10.1055/s-0034-1368168
|View full text |Cite
|
Sign up to set email alerts
|

Aspidosperma Species as Sources of Antimalarials. Part III. A Review of Traditional Use and Antimalarial Activity

Abstract: Yes See l " Table 2 A. ramiflorum Müll. Arg. Accepted name Syn. Geissospermum ramiflorum (Müll. Arg.) Miers [26] Pau-pereira, Peroba, Guatambú-amarelo Bolívia, Brazil: Amazonia Cerrado, Atlantic Rainforest Yes [22] Yes See l " Table 2 A. rigidum Rusby Accepted name Syn. A. acreanum Markg. (+ several others) [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…However, the most cited species in the Amazon used as a remedy against malaria is A. nitidum, which has proven to be the most active species based on its specific activity (Penna- Coutinho et al, 2013), superior than the other species less cited as antimalarial, such as A. ollivaceum, also studied by the same group (Chierrito et al, 2014). Other species tested showed variable in vitro activity against the P. falciparum with IC 50 values ranging from 0.019 to 42 µM (Brandão et al, 1985;Carvalho et al, 1992;Mitaine-Offer et al, 2002;Paula et al, 2014;Torres et al, 2013). The biological activity of the genus has been attributed to indole alkaloids (Frederich et al, 2008;Vieira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, the most cited species in the Amazon used as a remedy against malaria is A. nitidum, which has proven to be the most active species based on its specific activity (Penna- Coutinho et al, 2013), superior than the other species less cited as antimalarial, such as A. ollivaceum, also studied by the same group (Chierrito et al, 2014). Other species tested showed variable in vitro activity against the P. falciparum with IC 50 values ranging from 0.019 to 42 µM (Brandão et al, 1985;Carvalho et al, 1992;Mitaine-Offer et al, 2002;Paula et al, 2014;Torres et al, 2013). The biological activity of the genus has been attributed to indole alkaloids (Frederich et al, 2008;Vieira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Uleine was demonstrated to be the major constituent in the alkaloid fraction of Aspidosperma parvifolium trunk bark and 15 other indole alkaloids have been identified along with uleine. The high chemical diversity of alkaloids from Aspidosperma species and the small number of these alkaloids that have been assayed for anti-malarial activity coupled to the traditional use of several species of this taxon to treat malaria in Brazil, as well as in other meso- and South American countries, make further investigations of plants in this genus of great interest in the quest for natural anti-malarial drugs [12]. …”
Section: Resultsmentioning
confidence: 99%
“…A recent review of the traditional use and anti-malarial activity of Aspidosperma species revealed several scientific bibliographical references on the use of 24 species to treat malaria/fevers, including Aspidosperma parvifolium , and to 19 Aspidosperma species that have had their extracts and/or alkaloids evaluated for in vitro and/or in vivo anti-malarial activity showing positive results. Only 20, out of more than 200 known indole alkaloids from Aspidosperma species have been assayed for anti-malarial activity, and variable levels of parasite inhibition have been reported [12]. …”
Section: Introductionmentioning
confidence: 99%
“…A series of monoterpene indole alkaloids, such as Kopsia , Strychnos ,– and Aspidosperma ,– which show abundant bioactivities (e.g. adrenergic blocking, anticancer, antiarrhythmic and anti‐malarial) share a common 1 H ‐pyrrolo[2,3‐ d ]carbazole tetracyclic indoline scaffold (Figure ). There are three factors that contribute to the complexity of these structures: (a) the polycyclic nature of the scaffolds, (b) the continuous stereocenters, and (c) the presence of quaternary centers.…”
Section: Introductionmentioning
confidence: 99%